Wearable Sensor and Its Application in Urban Landscape Design. (10th August 2022) - Yao, Di
Abstract : In order to meet the needs of people for the environment, physical, and psychological needs and to improve the characteristics of local areas, this paper proposes an urban environment measurement method based on wearable sensors. This method mainly relies on the previous questionnaire and tests the wearable sensor physiological data, subjective feelings, scoring tables, interviews, and other experimental methods in the psychological experimental environment. The recognition rate without adding association features was 93.3%, while the recognition rate of adding association features to individual test set verification reached 94.1%, an increase of about 1%. In this paper, naive Bayes and associated feature classification are used to effectively solve the influence of personal subjective factors and make up for the error of measurement data. The wearable sensor can achieve better results in the application of urban environmental measurement and can also be better applied in urban environmental landscape design, providing more effective data for urban landscape design.